2023
DOI: 10.1039/d2me00187j
|View full text |Cite
|
Sign up to set email alerts
|

Current rectification by nanoparticles in bipolar nanopores

Abstract: Bipolar nanochannels comprising two domains of positively and negatively charged walls along the pore axis are known to rectify current when exposed to an electric potential bias. We find that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…This phenomenon is not observed in the +2 V case, therefore, it results in a very large rectification ratio for the case of an electrolyte with NaCl and charged nanoparticles when ϵ = 78.9. Note that we have previously shown that at the concentration of nanoparticles that we use here (0.7 mM), their direct contribution to the electric current is always less than 1% . The increase in current rectification caused by the addition of nanoparticles is related to their effect on the charge distribution inside the channel, as discussed in more detail below.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…This phenomenon is not observed in the +2 V case, therefore, it results in a very large rectification ratio for the case of an electrolyte with NaCl and charged nanoparticles when ϵ = 78.9. Note that we have previously shown that at the concentration of nanoparticles that we use here (0.7 mM), their direct contribution to the electric current is always less than 1% . The increase in current rectification caused by the addition of nanoparticles is related to their effect on the charge distribution inside the channel, as discussed in more detail below.…”
Section: Resultsmentioning
confidence: 67%
“…From a practical perspective, we consider the presence of nanoparticles because they might already be present in the water bodies used in membrane-based RED processes for energy generation. Moreover, we have observed in our previous work that low concentrations of nanoparticles can, under certain conditions, increase current rectification in bipolar nanopores . Here, we report simulations at two levels of description.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…[15] and was later modified by replacing the UP channels with conical channels carrying a BP inhomogeneous surface charge [39], positive at the base and negative at the tip. BP fluidic channels and (Janus) membranes have long drawn great interest as current rectifiers [42][43][44][45][46][47] for applications in e.g. sensing [47] and osmotic energy conversion [47][48][49].…”
Section: Iontronic Circuit and Bp Channelsmentioning
confidence: 99%